2022
DOI: 10.1111/psyp.14015
|View full text |Cite
|
Sign up to set email alerts
|

Safety on demand: Post‐hypnotic suggestions of safety reduce neural signals of reward sensitivity with long‐term beneficial effects

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 111 publications
3
15
0
Order By: Relevance
“…This result was interpreted as indicating less impulsive unhealthy choices under the influence of the PHS, which were implemented through effortful choice suppression. Further, our results showed qualitative and quantitative persistence of the PHS effects, at least over a period of 1 week, which is in line with other findings (Bohmer and Schmidt, 2022 ). Finally, our results revealed correlations between the PHS effects and hypnotizability, a multifactorial construct (Zahedi and Sommer, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result was interpreted as indicating less impulsive unhealthy choices under the influence of the PHS, which were implemented through effortful choice suppression. Further, our results showed qualitative and quantitative persistence of the PHS effects, at least over a period of 1 week, which is in line with other findings (Bohmer and Schmidt, 2022 ). Finally, our results revealed correlations between the PHS effects and hypnotizability, a multifactorial construct (Zahedi and Sommer, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our Bayesian results confirmed that the observed effects of the PHS were not diminishing over a period of more than 1 week. Even though some anecdotal reports suggest the longevity of PHS effects (for review, see Zahedi et al, 2017 ; Bohmer and Schmidt, 2022 ), few studies have investigated the question. For instance, Bohmer and Schmidt (Bohmer and Schmidt, 2022 ) have shown that a safety-promoting PHS was effective over several weeks ( Median = 49 days, Range = 7169 days ) after hypnosis induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval between Session 2 and Session 3 appears to be justified considering the effects of PHS in other contexts. For instance, Böhmer and Schmidt ( 32 ) have shown that a safety-promoting PHS was effective even over several weeks (Median = 49 days, Range = 7–169 days) after the hypnosis induction.…”
Section: Methodsmentioning
confidence: 99%
“…After these encouraging results, I decided to link the feeling of safety to a post-hypnotic trigger ( Böhmer and Schmidt, 2022 ). I wanted to investigate whether this could trigger the feeling of being in a safe place in the long term without the need for another therapeutic session.…”
Section: Feeling Safe With Hypnosismentioning
confidence: 99%